Concepts of programming languages - Sebesta, Robert W. (Boston : Addison-Wesley, 2010)
Concepts of Programming Languages introduces students to the main constructs of contemporary programming languages and provides the tools needed to critically evaluate existing and future programming languages. Readers gain a solid foundation for understanding the fundamental concepts of programming languages through the author's presentation of design issues for various language constructs, the examination of the design choices for these constructs in some of the most common languages, and critical comparison of the design alternatives. In addition, Sebesta strives to prepare the reader for the study of compiler design by providing an in-depth discussion of programming language structures, presenting a formal method of describing syntax, and introducing approaches to lexical and syntactic analysis.
Chapter 1 Preliminaries -- Chapter 2 Evolution of the Major Programming Languages -- Chapter 3 Describing Syntax and Semantics -- Chapter 4 Lexical and Syntax Analysis -- Chapter 5 Names, Bindings, and Scopes -- Chapter 6 Data Types -- Chapter 7 Expressions and Assignment Statements -- Chapter 8 Statement-Level Control Structures -- Chapter 9 Subprograms -- Chapter 10 Implementing Subprograms -- Chapter 11 Abstract Data Types and Encapsulation Constructs -- Chapter 12 Support for Object-Oriented Programming -- Chapter 13 Concurrency -- Chapter 14 Exception Handling and Event Handling -- Chapter 15 Functional Programming Languages -- Chapter 16 Logic Programming Languages.
Includes bibliographical references (p. 737-746) and index.
1
Keywords: Programming languages (Electronic computers)